Development of Group Counseling Guidelines for Student Self Control Improvement in Prevention of Drug Abuse - Liza Fidiawati; Firman Firman; Solfema Solfema (Jurnal Aplikasi IPTEK Indonesia, 2020)
The drug abuse in adolenscent circle, at Vocational High School,  is increasing significantly. The group of counceling service in a school is rarely used for preventing drug abuse. Most of the group counceling is used for solving about some problems, such as learning, personal, social, and career problem. This study is aimed to procude a simple, valid, and efective guidlines for the counceling group, to improve students self control in preventing drug abuse. This study is a development (Research and Development) with ADDIEmodel (Analyze, Design, Development, Implementation and Evaluation). TheSubjectof this study is the students at Vocational High School and the counceling teacher in school. The validity of this study is done by six experts who is related to this study and the guidlines display. The usability test is done by three of the counceling teacher. The data  analysis is descriptive and inferensial analysis with Koefisien Kendals statistic test. The study shows that: (1) The level of material suitability is very receivable with 93 percentage and guidlines display is also in proper category with 91 percentage, (2) The using of group counseling guidlines for improving students self control too prevent a drug abuse is in the best category with 87 percentage. It concludes that, this guidlines is proper to used by the counceling teacher and councelor as a tools in doing counceling in a counceling group as an effort to improve student self control in preventing a grud abuse.